Flicka : country pride [videorecording (DVD)] - Hartman, Lisa, 1956-; Black, Clint; Rohl, Kacey; Black, Lily Pearl; Dolphin, Connie; Robinson, Jen; Damian, Michael, 1962-; O'Hara, Mary (20th Century Fox Home Entertainment, 2012)
Toby takes a job at a stable with Flicka in tow. The owner's teenage daughter Kelly quickly bonds with the horse and hopes to break Flicka for an upcoming competition. With a rival trainer stealing business and a growing fear they may be forced to sell the stable, Toby steps in to turn things around for Kelly and her mother.